Meaning of hospitalization due to covid-19: A methodological approach in grounded theory (Revista Contexto & Saúde, 2025)
This study aimed to understand the meanings attributed to hospitalization by individuals who experienced moderate and severe forms of COVID-19. It is a qualitative study conducted with 19 individuals who had moderate and severe cases of COVID-19 in a municipality in the northwest region of the state of Paraná, from April to November 2021. The study was based on the theoretical framework of Symbolic Interactionism and employed the Constructivist Grounded Theory as its methodological approach. Data collection was carried out through individual interviews mediated by technology. The analysis followed open and focused coding, as proposed by the analytical method. The results indicate that both positive and negative meanings were constructed during hospitalization due to COVID-19. The influence of healthcare professionals was essential in fostering positive feelings toward the hospital environment, the disease, and the hospitalization units, as well as reinforcing the individual's role as an active agent in their recovery. Negative feelings such as fear and despair were also observed, both regarding the severity of the disease and the care received, due to healthcare professionals' lack of experience in handling COVID-19. Given the high number of hospitalizations, fear of hospital discharge was also significant, as patients were concerned about potential deterioration in their condition that might require readmission. The participants' experiences during the pandemic can serve as a foundation for understanding and formulating healthcare policies in public health emergencies.